Russia/Nigeria Diplomatic Ties: An Historical Perspective - Waliyullahi, Abimbola Damilola (European Scientific Journal, ESJ, 2016)
The Diplomatic relations between Nigeria and USSR (Union of Soviet Socialist Republics) now Russia started over 55 years ago. Russia, being the legitimate heir to the USSR in 1961, opened its Embassy in Lagos with Ambassador Feodor Pavlovich Dolya as the Head of the Mission, Nigeria reciprocated in 1962 in Moscow with Ambassador C.O Ifeagwu as the Head and till this day, both countries have maintained cordial political, economic and cultural relationships but not without some disagreements. However, Soviet involvement in Nigeria, just like in many other African countries diminished greatly in the wake of Mikhail Gorbachev’s perestroika (reconstruction) of the middle 80s. With the Cold War continuing and the Soviet economy in shambles, the USSR had little incentive to continue its active presence in Africa. By the time of Soviet Union disintegration in 1991, the country had lost much of its influence and prominence in Nigeria and Africa. Nigeria is a focus of this paper as this article examines Russia/Nigeria diplomatic ties from the historical point of view relying on diplomatic theory as a tool to trace the existing diplomatic ties between the two countries.